PEMANFAATAN BELALANG SEBAGAI SUMBER KITIN MELALUI PROSES EKSTRAKSI RAMAH LINGKUNGAN - Anjani, Cindy Salsabilla; Umam, Hilman Imadul; Pambudi, Teguh; Fauzie, Azis Kemal; Putri, Fajar Amelia Rachmawati (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
This study aimed to extract chitin from rice grasshoppers using the Deep Eutectic Solvent (DES) method. The chitin extraction process involves several stages, namely delipidation, demineralization, and deproteination. In the demineralization and deproteination stages, two extraction methods were compared, namely the conventional method using strong acids and bases and the environmentally friendly method using Deep Eutectic Solvent (DES). The conventional method uses hydrochloric acid (HCl) for demineralization and sodium hydroxide (NaOH) for deproteination. DES is an effective solvent in dissolving proteins without damaging the chitin structure. This success was evidenced by test parameters of fat content from 30.91 to 9.01 with a DL percentage of 70.85%. In the ash content test, it was proven that the % ash content in pure grasshoppers was 4.87% and decreased in the demineralization process to 1.38% for the extraction stage using DES from 1.25 in the extraction process using the conventional method, this shows that the demineralization extraction process was successful in reducing mineral levels. In the protein content test, pure grasshoppers were 53.57% decreased in the deproteination process using DES to 1.11% and in the conventional method using NaOH, it decreased by 1.65%, this proves a decrease in protein content in the deproteination stage. In the chitin extraction process, an infrared spectrum analysis (FTIR) was also carried out on the extracted chitin samples.